Union rate and clinical outcomes of second-try scaphoid reconstructions after failed primary scaphoid osteosynthesis or reconstruction. A retrospective, single-center cohort study of 52 patients - Rachunek-Medved, K.; Illg, C.; Einzmann, A.; Thiel, J. T.; Daigeler, A.; Medved, F. (Frontiers in Surgery, 2025)
IntroductionScaphoid non-union after failed primary surgery presents significant therapeutic challenges.MethodsIn this retrospective study, 52 patients (50 males; mean age 29.5 years) underwent secondary reconstructions (2009–2020) for proximal pole (38.5%, n = 20) and waist non-unions (61.5%, n = 32). Treatments included non-vascularized iliac crest grafts (17 patients), vascularized pedicled distal radius grafts (26), and free medial femoral condyle flaps (9). Union and scaphoid alignment were assessed by CT, while carpal alignment and arthrosis were evaluated using radiographs. Statistical analysis employed chi-square, Fisher's exact, Mann-Whitney U, and McNemar tests (R v4.4.2; p ≤ 0.05).ResultsUnion rates differed significantly between proximal pole (40%, 8/20) and waist non-unions (68.75%, 22/32; p = 0.04). Graft type (p = 0.616), osteosynthesis method (p = 0.827), age (p = 0.095), smoking (p = 0.582), avascular necrosis (p = 0.42), and prior surgeries (p = 0.974) showed no significant association with union. Proximal pole non-unions with AVN trended toward lower union (22.2% vs. 54.5% without AVN), though this was not statistically significant. In patients achieving union, scaphoid humpback deformity was corrected in 9/15 cases (p = 0.0348), and dorsal intercalated segment instability improved significantly (p = 0.0143). Functionally, the union group had an average extension-flexion of 112° (81% of the healthy wrist) and radial-/ulnar adduction of 40° (72% of the unaffected wrist), with grip strength averaging 42 kg (range 25.2-59.7) and a DASH score of 11 (range 0–67). The non-union group showed 114° extension-flexion (91% of the unaffected wrist) and 38° ulnar/radial abduction (78% of the healthy wrist), with grip strength averaging 46 kg (range 37.6-59.3; 89% of the unaffected wrist) and a DASH score of 10 (range 3–33).DiscussionSecondary scaphoid reconstruction demonstrates location-dependent success. The decision between secondary reconstruction, which aims to restore anatomical integrity, and salvage procedures, which prioritize predictable outcomes, hinges on balancing union potential, functional results, and patient preferences. A tailored approach remains essential to align treatment goals with individual needs.